Senegal : Fifth Review Under the Policy Support Instrument and Request for Program Extension and Modification of Assessment Criteria-Staff Report; Debt Sustainability Analysis; Informational Annex; and Press Release. (IMF Staff Country Reports; Country Report ;, 2013)
Program implementation has been satisfactory, and all assessment criteria were met. The fiscal deficit was reduced to 5.9 percent of GDP despite a significant revenue shortfall. Delays were incurred in the implementation of reforms in the energy sector. The authorities intend to accelerate reforms to improve the business environment by streamlining expenditure and by improving the efficiency of the state to reduce the fiscal deficit to below 4 percent of GDP by 2015. This will restore fiscal buffers and ensure long-term debt sustainability.